PENGARUH KARAKTERISTIK PEKERJAAN DAN PENGARUH KOMITMEN ORGANISASIONAL DENGAN BUDAYA ORGANISASI SEBAGAI MODERASI (Studi pada Personil Bersertifikat Pengadaan Barang/Jasa di Lingkungan Pemerintah Daerah Kota Tegal) - Haryono, Haryono; Tjahjaningsih, Endang (Jurnal Ilmiah Telaah Manajemen, 2018)
The research objective is to examine and analyze the influence of job characteristics and the influence of organizational commitment on performance with organizational culture as moderation.Respondents in this study were certified personnel in procurement of goods / services in the Tegal City Government. Data collection using census method as many as 117 respondents in the form of questionnaires with validity and reliability testing techniques and test the relationship between variables with mutiple regression models. The results showed that job characteristics and organizational commitment had a positive and significant effect on performance, organizational culture proved to be a moderating variable and strengthened the influence of job characteristics and organizational commitment on performance. Keywords: job characteristics, organizational commitment, organizational culture, performance